Palm OS Web application developer's guide developing and devilering PQAs and Web clipping - Combee, Ben. (Rockland, Mass. : Syngress Media ; London : International Thomson (distributor), 2001)
With an 80% hand-held device market-share, the Palm Organizer is the platform of choice for Mobile Internet application developers. With its decision to license the Palm OS to rival device manufacturers such as Sony, Motorola, and Handspring, Palm has further strengthened its claim as the industry standard for Mobile Computing architecture. Palm OS Web Application Developers Guide provides step-by-step instructions on how to migrate existing HTML to the Palm platform. The book will be useful for webmasters looking to convert current web pages. It is also ideal for C and Java programmers interested in building more dynamic applications from the ground up. The CD-ROM includes all the source code from book, PQA executable file and Palm OS emulators A timely release: With 8 million devices in use, thousands of developers are moving into this lucrative market Topic appeals to many segments of the market, including application developers, Internet Service Providers, and HTML proficient power-users Covers Web Clipping which has the power to convert existing HTML to the PQA format Focuses on the key challenges of creating web pages for a small viewing area in black and white.
Includes index.
Keywords: PalmPilot (Computer) -- Programming; PalmPilot (Computer) -- Computer programs; Web site development; Palm (Operating system); Electronic books